The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1364/oe.20.00a465
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication and optical characterization of photonic crystal assisted thin film monocrystalline-silicon solar cells

Abstract: In this paper, we present the integration of an absorbing photonic crystal within a monocrystalline silicon thin film photovoltaic stack fabricated without epitaxy. Finite difference time domain optical simulations are performed in order to design one- and two-dimensional photonic crystals to assist crystalline silicon solar cells. The simulations show that the 1D and 2D patterned solar cell stacks would have an increased integrated absorption in the crystalline silicon layer would increase of respectively 38%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…60-80 nm) [1,4,5,11,12]. Figure 4 shows the impact of the filling factor f f on the degradation ratio r. These simulations showed that it was not influenced by the orientation of the PC since we had exactly the same results (Fig.…”
Section: Behavior Of the Local Sheet Resistancementioning
confidence: 53%
See 2 more Smart Citations
“…60-80 nm) [1,4,5,11,12]. Figure 4 shows the impact of the filling factor f f on the degradation ratio r. These simulations showed that it was not influenced by the orientation of the PC since we had exactly the same results (Fig.…”
Section: Behavior Of the Local Sheet Resistancementioning
confidence: 53%
“…The objective is to mimic nanopatterns like inverted nanopyramids (fabricated by wet etching [1,5,11]) and cylindrical nanoholes (obtained by dry etching [4,5,11,12]), covered by a partial TCO layer. Figure 3 represents the electric periodic elements for a PC made of a square lattice of squares, rounds and diamonds with a top finger aligned (a) or not (b) with the PC directions.…”
Section: Behavior Of the Local Sheet Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…For the case of mono-crystalline silicon, periodic photonic nanostructures have been barely investigated optically but they have not been integrated in a solar cell so far [17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Here, the nanocups pattern is selfassembled by hole-mask colloidal lithography, where the electrostatic forces result in a short-range order, featuring a near-neighbor distance Gaussian distribution [19]. With a peak at ∼580 nm and nanocups diameter of ∼600 nm, it presents for this film thickness the best compromise between light in-coupling, associated with small near-neighbor distances, and light-trapping of low-energy photons, requiring larger pitches [27][28][29]. Further, the nanocup depth-profile is a rounded square-based pyramid with the aspect ratio (length by diameter) of 0.9-1 and, importantly, without negative slopes (atomic-force microscopy (AFM) scans can be found in the supporting materials, figure S2).…”
mentioning
confidence: 99%